“A most bountiful source of inspiration:” Dobzhansky’s evolution of tropical populations, and the science and politics of genetic variation - Tito Carvalho (História, Ciências, Saúde: Manguinhos)
Abstract Theodosius Dobzhansky has been studied for how he integrated field naturalism and laboratory experimentation in ways that helped produce the Modern Synthesis, as well as how he leveraged biological expertise to support liberal and cosmopolitan values amidst Second World War and the Cold War. Moreover, Dobzhansky has been central in analyses of the institutionalization of genetics in Brazil, where he spent several years. This article situates Dobzhansky’s Brazilian research within the science of variation and the politics of diversity. I conclude by raising questions about how the ways in which science figured in politics depended on ideas about the role of scientists in society whichwere advanced in parallel, suggesting research on the “co-production” of natural and social orders.